Occurrence and Distribution of Wood Decaying Fungi in Forest Wood Depots of Chhattisgarh - Tiwari, C. K.; Parihar, Jagrati; Verma, R. K. (Indian Forester, 2010)
The occurrence and distribution of 81 wood decaying fungi on different hosts in forest wood depots of Chhattisgarh is reported. The study area is confined to nine wood depots and each wood depot, depending on area occupied, is divided into five sectors. The maximum number of wood decaying fungi reported in Gariyabandh wood depot and minimum number of wood decaying fungi reported in Kota and Dhamtari. Out of 79 specimens, 3 species including Schizophyllum commune Fr., Trametescingulata Berk. and Flavodonflavus (Klot.) Ryvarden, were common to all nine wood depots areas and show their occurrence and frequency 100%.